Bisphosphonates and their indication to prevent bone density loss in cancer therapy (Research, Society and Development, 2022)
Aim: To establish a protocol for patients medicated with bisphosphonates, through literature review, to avoid osteonecrosis and to provide professional guidance to accomplish the appropriate treatment. Methodology: On line searches were accomplished for the construction of this paper, which included as databases Web of Science, PUBMED Central, BVS/BIREME, Science Direct, The Cochrane Library and also PROSPERO. Results: The following characteristics were observed in the research of this protocol: Drugs with antireabsorption properties, RANK-L Inhibitor, Antiangiogenic agents, Clinical Manifestations, Drug-related risk factors, Local risk factors to be observed, Systemic and demographic risk factors, High risk factors considered. Conclusions: Bisphosphonates may be a helpful therapy for patients with organic consequences related to the therapy applied with them. Appropriate anamnesis and assessment of the systemic conditions for patients using them are mandatory requirements before their prescription.